Redundant residue number system based space-time block codes - Sengupta, Avik (Kansas State University, 2012)
Space-time coding (STC) schemes for Multiple Input Multiple Output (MIMO) systems have been an area of active research in the past decade. In this thesis, we propose a novel design of Space-Time Block Codes (STBCs) using Redundant Residue Number System (RRNS) codes, which are ideal for high data rate communication systems. Application of RRNS as a concatenated STC scheme to a MIMO wireless communication system is the main motivation for this work. We have optimized the link between residues and complex constellations by incorporating the “Direct Mapping” scheme, where residues are mapped directly to Gray coded constellations. Knowledge of apriori probabilities of residues is utilized to implement a probability based “Distance-Aware Direct Mapping” (DA) scheme, which uses a set-partitioning approach to map the most probable residues such that they are separated by the maximum possible distance. We have proposed an “Indirect Mapping” scheme, where we convert the residues back to bits before mapping them. We have also proposed an adaptive demapping scheme which utilizes the RRNS code structure to reduce the ML decoding complexity and improve the error performance. We quantify the upper bounds on codeword and bit error probabilities of both Systematic and Non-systematic RRNS-STBC and characterize the achievable coding and diversity gains assuming maximum likelihood decoding (MLD). Simulation results demonstrate that the DA Mapping scheme provides performance gain relative to a Gray coded direct mapping scheme. We show that Systematic RRNS-STBC codes provide superior performance compared to Nonsystematic RRNS-STBC, for the same code parameters, owing to more efficient binary to residue mapping. When compared to other concatenated STBC and Orthogonal STBC (OSTBC) schemes, the proposed system gives better performance at low SNRs.
Keywords: MIMO systems; Redundant residue number system; Space time block bode; Distance aware mapping; Electrical Engineering (0544)